2017
DOI: 10.1007/s00223-017-0322-z
|View full text |Cite
|
Sign up to set email alerts
|

Bone Disease in Connective Tissue Disease/Systemic Lupus Erythematosus

Abstract: This article reviews recent advances in the research of the mechanisms of bone loss, as well as clinical features, economic impact and therapeutic implications of osteoporosis and fractures in patients with systemic lupus erythematosus (SLE) as an illustration of bone disease in a complex systemic autoimmune connective tissue disease. Recent studies demonstrated an increased incidence of osteoporosis and peripheral and vertebral fractures in patients with SLE. The aetiology of bone loss in SLE is multifactoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 96 publications
1
73
0
4
Order By: Relevance
“…Osteoporosis and fragility fractures occur frequently among SLE patients, being also present in juvenile SLE patients, men and premenopausal women, population groups usually at low risk. SLE is associated with an increased risk for osteoporosis and vertebral fractures, with a prevalence of morphometric vertebral fracture ranging from 14% to 50% in patients with a mean age around 40 2. In particular, a recent very large, population-based study on over 47 000 patients reported SLE to be associated to a twofold increased risk for fracture, threefold in case of lupus nephritis.…”
mentioning
confidence: 99%
“…Osteoporosis and fragility fractures occur frequently among SLE patients, being also present in juvenile SLE patients, men and premenopausal women, population groups usually at low risk. SLE is associated with an increased risk for osteoporosis and vertebral fractures, with a prevalence of morphometric vertebral fracture ranging from 14% to 50% in patients with a mean age around 40 2. In particular, a recent very large, population-based study on over 47 000 patients reported SLE to be associated to a twofold increased risk for fracture, threefold in case of lupus nephritis.…”
mentioning
confidence: 99%
“…This dialogue, although still partially undeciphered, represents a promising research field, since its understanding could provide new insights for the design of targeted therapeutic strategies for osteoporosis [12]. Most of the pathologies causing osteoporosis are characterized by a chronic inflammatory background [13][14][15]. The menopausal estrogen decline and the aging process induce osteoporosis, mainly increasing the production of inflammatory cytokines that exert osteoclastogenic properties [9].…”
Section: Osteoporosis and The Cytokine Regulation Of Bone Remodelingmentioning
confidence: 99%
“…Osteoporosis is a source of chronic pain and disability which contributes to morbidity and is a major challenge to the quality of life. SLE is significantly associated with lower bone mineral density (BMD) levels and with an increased fracture risk at all sites, especially vertebral fractures,35–37 which are often asymptomatic 35. The aetiology of bone loss and fractures is multifactorial in SLE, including GC therapy, disease activity, early menopause (such as in patients treated with intravenous cyclophosphamide), vitamin D deficiency (related to photoprotection) and frailty 35.…”
Section: Introductionmentioning
confidence: 99%
“…This should include an evaluation of dietary calcium intake, consumption of bone toxics (tobacco, alcohol and excess salt intake), a search for risk factors for fracture risk estimation (personal history of low trauma fracture) as well as a systematic measurement of BMD in all patients with SLE, including men and children aged 7+ 36. If BMD is abnormal, an X-ray examination of the dorsal and lumbar spine should be performed, searching for asymptomatic prevalent fractures 35. The detection of one or more asymptomatic prevalent vertebral fracture with at least osteopaenia is an indication for antiosteoporotic treatment.…”
Section: Introductionmentioning
confidence: 99%